2014
DOI: 10.1021/la500822w
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich Antibody Arrays Using Recombinant Antibody-Binding Protein L

Abstract: Antibody arrays are a useful for detecting antigens and other antibodies. This technique typically requires a uniform and well-defined orientation of antibodies attached to a surface for optimal performance. A uniform orientation can be achieved by modification of antibodies to include a single site for attachment. Thus, uniformly oriented antibody arrays require a bioengineered modification for the antibodies directly immobilization on the solid surface. In this study, we describe a “sandwich-type” antibody a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Recently, Poulter and co-workers achieved highly ordered, regioselective immobilization of the glutathione S-transferase enzyme and antibody-binding protein G to self-assembled monolayers on gold surfaces . They further created sandwich antibody arrays of immobilized recombinant antibody-binding protein L for capturing antibodies for direct- and sandwich-type immunofluorescent detection of ligands in a microarray format . In general, the prenylation-based immobilization strategy has several potential biomedical and biotechnology applications where oriented protein immobilization is required, such as protein arrays, and diagnostic applications based on immunoassays, surface plasmon resonance (SPR), or electrochemical methods.…”
Section: Biotechnological Applicationsmentioning
confidence: 99%
“…Recently, Poulter and co-workers achieved highly ordered, regioselective immobilization of the glutathione S-transferase enzyme and antibody-binding protein G to self-assembled monolayers on gold surfaces . They further created sandwich antibody arrays of immobilized recombinant antibody-binding protein L for capturing antibodies for direct- and sandwich-type immunofluorescent detection of ligands in a microarray format . In general, the prenylation-based immobilization strategy has several potential biomedical and biotechnology applications where oriented protein immobilization is required, such as protein arrays, and diagnostic applications based on immunoassays, surface plasmon resonance (SPR), or electrochemical methods.…”
Section: Biotechnological Applicationsmentioning
confidence: 99%
“…The antigen-bound slides could be reused by treatment with acidic buffer to strip away the antibody layer while leaving the covalently immobilized antigens attached for use in another round of protein detection. In a follow-up paper, they showed that their “sandwich-type” antibody arrays that exhibit regioselectively immobilized antigens show superior properties compared to randomly oriented antigens immobilized on commercially epoxy-modified slides . As described in their previous work, a sandwich structure for detecting GFP was constructed by immobilizing an alkyne-functionalized recombinant protein L onto azide-glass slides, followed by incubation with a mouse anti-GFP IgG antibody.…”
Section: Proteins Of Interest Site-specifically Functionalized Via Li...mentioning
confidence: 97%
“…In a follow-up paper, they showed that their "sandwich-type" antibody arrays that exhibit regioselectively immobilized antigens show superior properties compared to randomly oriented antigens immobilized on commercially epoxy-modified slides. 546 As described in their previous work, a sandwich structure for detecting GFP was constructed by immobilizing an alkyne-functionalized recombinant protein L onto azide-glass slides, followed by incubation with a mouse anti-GFP IgG antibody. Captured GFP was detected with DyLight 680-labeled mouse anti-GFP IgG with high sensitivity and low cross-reactivity against the components of the sandwich array.…”
Section: C-terminal Protein Functionalization Through S-prenylationmentioning
confidence: 99%
“…262 In 2013, they constructed antibody arrays by immobilizing antibody binding proteins A, G and L onto glass slides using a similar strategy, 157,263 enabling antibody capturing for direct and sandwich-type immunofluorescent antigen detection. Besides glass slides, proteins labelled with alkyne isoprenoid analogues can also be deposited onto the azide-modified self-assembled monolayers prepared on the gold surfaces using the CuAAC reaction, as illustrated by the Poulter 264 and Maynard 265 groups, respectively.…”
Section: Enzymatic Protein Labelling Strategiesmentioning
confidence: 99%